Physical Principles of Photocurrent Generation in a Silicon-Based Photodiode Structure with a Schottky Barrier - Giyasova , Feruza A.; Rakhmatov, Akhmad Z.; Bakhronov, Khayot N.; Yuldoshev, Murodjon A.; Giyasov, Farkhod A.; Olimov, Abdurauf N.; Sattarov, Nosirbek A. (East European Journal of Physics, 2025)
Homojunction structures of the type Ag–nSi–n⁺Si–(In+Sn) with perfect single-crystal (111) orientation and a high-resistivity compensated layer at the n⁺Si/n-Si interface were obtained using the liquid-phase epitaxy method. The results of investigating photogeneration processes and current transport mechanisms in the silicon Schottky-barrier photodiode structure are presented. A two-barrier model of the structure was developed, according to which current transport has a multifactorial nature and is governed by the combined contributions of thermionic emission, tunneling, and generation–recombination processes. Furthermore, it was established that the photosensitivity of the studied structure covers a photon energy range of 0.387÷1.016 eV, shifted toward the long-wavelength region. The formation of a near-surface high-resistivity layer contributes to an increased response and enables photosensitivity values of up to 0.338 A/W. It was found that reducing the barrier capacitance to 8÷10 pF broadens the frequency range and enhances the speed of response. The Ag–nSi–n⁺Si–(In+Sn) structures are promising for use in photodiodes of optoelectronic devices operating in the visible and infrared spectral regions.